For underlying asset $$d S = r S dt + \sigma S d W + (J-1)Sd N$$ here $W$ is a Brownian motion, $N(t)$ is Poisson process with intensity $\lambda.$

Suppose $J$ is log-normal with standard deviation $\sigma_J,$ denote $$k = E[J-1]$$ then the value of vanilla call is $$\sum\limits_{n=0}^{\infty}\dfrac{(\lambda'\tau)^n}{n!}e^{-\lambda'\tau}V_{BS}(S,t;\sigma_n,r_n)$$ Here $$\lambda' = \lambda(1+k),\ \tau =T - t$$ $$\sigma^2_n = \sigma^2 + \dfrac{n\sigma_J^2}{\tau},\ r_n=r-\lambda k+\dfrac{n\log(1+k)}{\tau}$$ and $V_{BS}$ is Black-Scholes value of a call without jumps.

The result seems to be the weighted mean of vanilla calls, but how to deduce this conclusion? Or is there any reference?

Suppose $\log J \sim N(\mu,\sigma^2_J)$ and $Z$ is standard normal, then we have \begin{eqnarray*} \log S_T &=& \log S_0 + (r - \dfrac{1}{2}\sigma^2)T + \sigma\sqrt{T} Z + N(T)\log(J)\\ &\sim& \log S_0 + \dfrac{1}{2}N(T)\sigma_J^2 +N(T)\mu + (r - \dfrac{1}{2}\hat{\sigma}^2)T + \hat{\sigma}\sqrt{T}Z\\ &=& \log \hat{S}_0 + (r - \dfrac{1}{2}\hat{\sigma}^2)T + \hat{\sigma}\sqrt{T} Z \end{eqnarray*} we omit the representations of $\hat{S}_0,\ \hat{\sigma}.$ So I think the price at $0$ should be $$\sum\limits_{n=0}^{\infty}\dfrac{(\lambda T)^n}{n!}e^{-\lambda T}V_{BS}(\hat{S}_0,0;\hat{\sigma}_n,r)$$

Why the author change the risk free rate $r_n$ and intensity $\lambda',$ does he change the measure for both Brownian motion and Poisson process?

  • 1
    $\begingroup$ See this question. $\endgroup$ – Gordon May 6 '17 at 16:28
  • $\begingroup$ Looks like the Merton model. $\endgroup$ – noob2 May 6 '17 at 22:03
  • 1
    $\begingroup$ Possible duplicate of Formula for Merton jump diffusion call price $\endgroup$ – LocalVolatility May 6 '17 at 22:39
  • $\begingroup$ please see the update @Gordon $\endgroup$ – A.Oreo May 7 '17 at 13:53
  • $\begingroup$ pls see the update @LocalVolatility $\endgroup$ – A.Oreo May 7 '17 at 13:53

We assume that the process $\{J_t, \, t\ge 0\}$ is defined at the jump times of the Poisson process $\{N_t, \, t \ge 0\}$, and all the jump sizes are independent and identically distributed. That is, \begin{align*} Q_t \equiv \int_0^t (J_t-1) dN_t = \sum_{n=1}^{N_t} (J_i-1), \end{align*} where $J_i$, for $i=1, \ldots, \infty$, are independent and $\xi_i = \ln J_i \sim N\left(u, \sigma_J^2\right)$. Note that, the process \begin{align*} Q_t -\lambda k\, t \end{align*} is a martingale. Moreover, as the discount stock price process $\{e^{-rt}S_t, \ t\ge 0\}$ is a martingale, under the risk-neutral measure, we assume that the stock price process $\{S_t, \, t \ge 0\}$ satisfies an SDE of the form \begin{align*} dS_t = S_t \Big[(r-\lambda k)dt + \sigma dW_t + dQ_t\Big]. \end{align*} Then, \begin{align*} S_T &= e^{\left(r-\lambda k-\frac{1}{2}\sigma^2\right)T + \sigma W_T} \prod_{i=1}^{N_T} J_i = e^{\left(r-\lambda k-\frac{1}{2}\sigma^2\right)T + \sigma W_T + \sum_{i=1}^{N_T} \xi_i}. \end{align*} Consequently, $n\ge 0$, \begin{align*} S_T\, \mathbb{I}_{N_T=n} &=e^{\left(r-\lambda k + \frac{n u}{T}-\frac{1}{2}\sigma^2\right)T + \sigma W_T + \sum_{i=1}^n (\xi_i-u)}\\ &=e^{\left(r-\lambda k + \frac{n u}{T}-\frac{1}{2}\sigma^2\right)T + \sqrt{\sigma^2 + \frac{n \sigma_J^2}{T}}\sqrt{T} Z}\\ &=e^{\left(r_n -\frac{1}{2}\sigma_n^2\right)T + \sigma_n \sqrt{T} Z}, \end{align*} where $Z$ is a standard normal random variable, $\sigma_n= \sqrt{\sigma^2 + \frac{n \sigma_J^2}{T}}$, and \begin{align*} r_n &= r-\lambda k + \frac{n u}{T}-\frac{1}{2}\sigma^2 +\frac{1}{2}\sigma_n^2\\ &= r-\lambda k + \frac{n\ln(1+k)}{T}. \end{align*}

Therefore, \begin{align*} e^{-rT}E\left((S_T-K)^+ \right) &=\sum_{n=0}^{\infty}e^{-rT}E\left((S_T-K)^+ \mathbb{I}_{N_T=n}\right)P(N_T=n)\\ &=\sum_{n=0}^{\infty}e^{(-r+r_n)T}e^{-r_nT}E\left((S_T-K)^+ \mathbb{I}_{N_T=n}\right)P(N_T=n)\\ &=\sum_{n=0}^{\infty}\frac{(\lambda T)^n}{n!}e^{-\lambda T}e^{(-r+r_n)T}C(S_0, K, r_n, \sigma_n, T)\\ &=\sum_{n=0}^{\infty}\frac{(\lambda T)^n}{n!}e^{-\lambda T}e^{\left(-\lambda k + \frac{n\ln(1+k)}{T}\right)T}C(S_0, K, r_n, \sigma_n, T)\\ &=\sum_{n=0}^{\infty}\frac{(\lambda T)^n}{n!}e^{-\lambda(1+k) T}e^{\left(-\lambda k + \frac{n\ln(1+k)}{T}\right)T}C(S_0, K, r_n, \sigma_n, T)\\ &=\sum_{n=0}^{\infty}\frac{(\lambda' T)^n}{n!}e^{-\lambda' T}C(S_0, K, r_n, \sigma_n, T), \end{align*} where $\lambda'=(1+k)\lambda$ and $C(S_0, K, r_n, \sigma_n, T)$ is the Black-Scholes option price.

  • $\begingroup$ Thanks a lot, why here is $d S = S_t\left((r- \lambda k)d t +\sigma d W + (J-1)d N_t\right)$? Under the original measure, I think it should be $d S = S_t\left((r+ \lambda k)d t +\sigma d W + ((J-1)d N_t - \lambda kd t\right) $ $\endgroup$ – A.Oreo May 8 '17 at 2:18
  • $\begingroup$ If you already have it in the end, you don't need it at the drift to have the martinaglity. $\endgroup$ – Gordon May 8 '17 at 11:04
  • $\begingroup$ but the given condition of $dS$ on the top have no $\lambda kdt$ in both $d N$ and $r,$ then the result should not be the given one. And I think $dS$ should write as $dS =S(rdt + \sigma(dW + \dfrac{\lambda k}{\sigma}dt) + ((J-1)dN - \lambda kdt),$ then change the measure. But we can no longer obtain the representation of $r_n$ bove. $\endgroup$ – A.Oreo May 8 '17 at 12:52
  • $\begingroup$ Sorry, I think my deduction is right, and after changing the measure, we have your representation of $dS.$ The last question is the method in my update not right? Since the discounted value of $S$ is not martingale, and we can't simple replace by $\hat{S}$ and $\hat{\sigma}.$ $\endgroup$ – A.Oreo May 8 '17 at 13:15
  • $\begingroup$ You can still work with the original process you provided and calculate the option price in a mathematical sense. However, note that, as $e^{-rt}S_t$ is not a martingale, the term $-\lambda k$ has to be added to the drifted to make it appropriate. $\endgroup$ – Gordon May 8 '17 at 13:16

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.